Non-surgical oral hygiene interventions on disease activity of Rheumatoid arthritis patients with periodontitis: A randomized controlled trial - William Buwembo; Ian Guyton Munabi; Mark Kaddumukasa; Haruna Kiryowa; Muhammad Mbabali; Ethel Nankya; William Evan Johnson; Emmy Okello; Nelson K. Sewankambo (Journal of Dental Research, Dental Clinics, Dental Prospects, 2020)
Background. Periodontitis and rheumatoid arthritis have similar epidemiology and pathophysiology. Understanding the interaction between these two diseases is vital in our settings. We set out to assess the effect of oral hygiene interventions on disease activity of rheumatoid arthritis patients with periodontitis in Kampala, Uganda. Methods. Fifty-eight patients attending an arthritis clinic with rheumatoid arthritis and periodontitis were randomly assigned to either an intervention group or a control group. Patients diagnosed with rheumatoid arthritis at least two years before, who were on the same medication, dose, or formulation for RA treatment during the preceding three months, were included. The patients were >18 years of age, would be available for all the study visits in the next six months, had at least six natural teeth, had periodontal disease classified as Dutch Periodontal Index (DPSI) >3 and provided written informed consent. Those who had a chronic disorder requiring chronic or intermittent use of antibiotics, were pregnant, were lactating, or had intent to become pregnant were excluded. The primary outcome measure was a change in Disease Activity Score of 28 Joints (DAS28 score) in two 3-month follow-up periods after the intervention. The secondary outcome measure was a change in periodontal status. Results. There was a statistically significant improvement in the DAS-28 score in both the intervention and control arms during the follow-up period (P<0.01). The participants carrying more than one bacterial species had worse DAS-28 scores. Conclusion. Oral hygiene interventions given to RA patients could drastically improve their RA treatment outcomes, especially in resource-limited settings.